Transformational Leader in Virtual Youtuber Commercial Business: Psychobiography of Motoaki “Yagoo” Tanigo - Wibowo, Rahmadina Syarafina; Milla, Mirra Noor (Yayasan Mata Pena Madani, 2025)
Psychobiography is widely known for a significant life-span study of an individual interpreted through the lens of relevant theories of psychology. This study aimed to examine the underlying mechanism of Yagoo’s transformational leadership as the CEO of Cover Corporation. Transformational leaders encompassed unique personalities that may be condemned by other competitive entrepreneurial leaders who are driven by the need for power and achievement. The underlying mechanism of transformational leadership was explained through the lens of Self-Determination Theory and Individual Entrepreneurship Orientation. The analysis was conducted using a qualitative approach and used secondary data sources such as written and recorded interviews. Triangulated data was utilized in terms of data credibility. Deductive thematic analysis showed Yagoo as a transformational leader established a sense of authenticity in developing his followers and community. This was achieved by fulfilling psychological basic needs, such as the need for autonomy, competency, and relatedness. Business dispositions, particularly innovativeness, proactiveness, and risk taking were present in Yagoo’s professional journey from the pioneering period towards the success in commercial business. The implication highlighted an understanding of the nature of a humanistic leader who engages in digital commercial activities.